2005
DOI: 10.1111/j.1365-2125.2005.02407.x
|View full text |Cite
|
Sign up to set email alerts
|

Profound weight loss associated with reboxetine use in a 44‐year‐old woman

Abstract: We report a case of significant weight loss experienced by a 44‐year‐old Caucasian woman treated with reboxetine. She was treated with this drug at 12 mg daily for a total duration of 11 months. During the corresponding period her body mass index (BMI) decreased from a baseline of 21.4 kg m−2 to a low of 16.8 kg m−2. Withdrawal of the drug led to a full recovery of her BMI. The strongest evidence linking reboxetine to this woman's weight loss laid in the fact that the re‐introduction of the drug subsequently c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 8 publications
1
6
0
Order By: Relevance
“…However, there is no information about the exact sequence of events in these reports. 5 Similar to our case, Lu et al [5] report a case of significant weight loss experienced by a 44-year-old woman treated with reboxetine. However their reported case had a number of comorbid medical disorders including chronic hepatitis C infection, rheumatoid arthritis, gastroesophageal reflux disease, and hypertension.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…However, there is no information about the exact sequence of events in these reports. 5 Similar to our case, Lu et al [5] report a case of significant weight loss experienced by a 44-year-old woman treated with reboxetine. However their reported case had a number of comorbid medical disorders including chronic hepatitis C infection, rheumatoid arthritis, gastroesophageal reflux disease, and hypertension.…”
Section: Discussionsupporting
confidence: 62%
“…The studies testing the effects of reboxetine on body weight have demonstrated that reboxetine reduces body weight [4]. However there are only a few cases in the literature of reboxetine use in adults resulting in profound weight loss [5]. We present an unusual case report of a patient who experienced a marked weight loss with reboxetine treatment, regained weight after its withdrawal and experienced marked weight loss after re-challenge with reboxetine.…”
Section: Introductionmentioning
confidence: 89%
“…Reboxetine is a selective norepinephrine reuptake inhibitor (NRI) and is a new psychotropic drug broadly used as an antidepressant and antianxiety agent, which has been reported to have effects on weight loss [ 21 ]. Lu et al reported a case significant weight loss treated with reboxetine at 12 mg daily for a total duration of 11 months [ 22 ]. Through stimulation of NE activity by the selective NRI, reboxetine is considered to diminish olanzapine induced weight gain [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…That means patients could get obese in spite of taking reboxetine for weight reduction, which reflects that the medication seems ineffective treatment option for weight reduction of patients prescribed atypical antipsychotics [ 23 ]. Reboxetine is known as a mediator of enhancing cognitive dysfunction in schizophrenia patients; long-term studies using higher dosages are needed to determine the role of reboxetine as cognitive enhancers in patients with schizophrenia and other disorders associated with cognitive impairments [ 22 , 23 ]. Conversely, in this review, the reboxetine group did not show statistical difference of psychiatric symptom improvement compared to the placebo group.…”
Section: Discussionmentioning
confidence: 99%
“…Reboxetine has not been evaluated in obese patients. However, a case of significant weight loss in normal weight woman treated with reboxetine was described 9 …”
Section: Centrally Acting Drugs That Affect Serotonin and Norepinephrmentioning
confidence: 99%